Exploring 12 to 14 year old children’s perceptions of the causes and effects of physical violence between children : a Lynedoch study - Demas, Grant (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Psychology))--University of Stellenbosch, 2010.